Idiopathic Granulomatous Mastitis Associated with Erythema Nodosum - Kalaycı, Tuğçe Özlem (Balkan Med J, 2016)
BACKGROUND: Idiopathic granulomatous mastitis (IGM) is an uncommon benign chronic inflammatory breast disease, and erythema nodosum (EN) is an extremely rare systemic manifestation of IGM. Here, we report a rare case of IGM accompanied by EN. CASE REPORT: A 32-year-old patient was admitted to our clinic with a history of a tender mass in the right breast. On physical examination, the right breast contained a hard, tender mass in the lower half with indrawing of the nipple. She had florid EN affecting both legs. She was evaluated with mammography, ultrasound, power Doppler ultrasound, non-enhancing magnetic resonance imaging (MRI), dynamic contrast-enhanced MRI, fine needle aspiration biopsy (FNAB) and excisional biopsy. Time-intensity curves showed a type II pattern on dynamic contrast-enhanced MRI, which has an intermediate probability for malignancy. The FNAB reported a benign cytology suggestive of a granulomatous inflammation, which was also supported by the histopathological findings. A partial mastectomy was performed following medical treatment. There was no recurrence at 1-year follow-up. CONCLUSION: IGM should be considered in the differential diagnosis of EN. Although histopathological examination remains the only method for the definite diagnosis of IGM, MRI can be helpful in the diagnosis or differentiation of benign lesions from malignant ones.